Transcriptome Analysis of Bread Wheat Genotype KRL3-4 Provides a New Insight Into Regulatory Mechanisms Associated With Sodicity (High pH) Tolerance - Prasad, Geeta; Mittal, Shikha; Kumar, Arvind; Chauhan, Divya; Sahu, Tanmaya Kumar; Kumar, Sundeep; Singh, Rakesh; Yadav, Mahesh C.; Singh, Amit Kumar (Frontiers in Genetics, 2022)
Globally, sodicity is one of the major abiotic stresses limiting the wheat productivity in arid and semi-arid regions. With due consideration, an investigation of the complex gene network associated with sodicity stress tolerance is required to identify transcriptional changes in plants during abiotic stress conditions. For this purpose, we sequenced the flag leaf transcriptome of a highly tolerant bread wheat germplasm (KRL 3-4) in order to extend our knowledge and better understanding of the molecular basis of sodicity tolerance. A total of 1,980 genes were differentially expressed in the flag leaf due to sodicity stress. Among these genes, 872 DEGs were up-regulated and 1,108 were down-regulated. Further, annotation of DEGs revealed that a total of 1,384 genes were assigned to 2,267 GO terms corresponding for 502 (biological process), 638 (cellular component) and 1,127 (molecular function). GO annotation also revealed the involvement of genes related to several transcription factors, important ones are expansins, peroxidase, Glutathione-S-transferase and metal ion transporters in response to sodicity. Additionally, from 127 KEGG pathways, only 40 were confidently enriched at p-value <0.05 covering the five main KEGG categories of metabolism, i.e., environmental information processing, genetic information processing, organismal systems and cellular processes. Most enriched pathways prioritized using MapMan software and revealed that lipid metabolism, nutrient uptake and protein homeostasis were paramount. We have also found 39 SNPs which mapped to the important sodicity stress responsive genes associated with various pathways such as ROS-scavenging, serine/threonine protein kinase, calcium signaling and metal ion transporters. In a nutshell, only 19 important candidate genes contributing to sodicity tolerance in bread wheat were identified and these genes might be helpful for better understanding and further improvement of sodicity tolerance in bread wheat.